La Crosse Virus Neuroinvasive Disease in Children: A Contemporary Analysis of Clinical/Neurobehavioral Outcomes and Predictors of Disease Severity - Boutzoukas, Angelique E; Freedman, Daniel A; Koterba, Christine; Hunt, Garrett W; Mack, Kathy; Cass, Jennifer; Yildiz, Vedat O; de Los Reyes, Emily; Twanow, Jaime; Chung, Melissa G; Ouellette, Christopher P (Clinical infectious diseases, 2023)
La Crosse virus (LACV) is the most common neuroinvasive arboviral infection in children in the United States. However, data regarding predictors of disease severity and neurologic outcome are limited. Additionally, long-term neurologic and neurobehavioral outcomes remain relatively sparse. This was a single-center, retrospective cohort study, followed by recruitment for a cross-sectional analysis of long-term neurobehavioral outcomes, among children aged 0-18 years with proven or probable LACV neuroinvasive disease (LACV-ND) between January 2009 and December 2018. Case ascertainment was assured by International Classification of Diseases, Ninth and Tenth Revision, Clinical Modification codes cross-referenced with laboratory results detecting LACV. Demographics, diagnostics, radiographs, and outcomes were evaluated. Recruitment of patients with prior diagnosis of LACV-ND occurred from January 2020 to March 2020, with assessment performed by validated pediatric questionnaires. One-hundred fifty-two children (83 males; median age, 8 years [interquartile range, 5-11.5 years]) were diagnosed with proven (n = 61 [47%]) and probable (n = 91 [60%]) LACV-ND. Sixty-five patients (43%) had severe disease. Altered mental status (AMS) (odds ratio [OR], 6.36 [95% confidence interval CI, 2.03-19.95]; P = .0002) and seizures at presentation (OR, 10.31 [95% CI, 3.45-30.86]; P = .0001) were independent predictors of severe disease. Epileptiform discharges on electroencephalogram (EEG) were independently associated with epilepsy diagnosis at follow-up (OR, 13.45 [95% CI, 1.4-128.77]; P = .024). Fifty-four patients were recruited for long-term neurobehavioral follow-up, with frequent abnormal assessments identified (19%-54%) irrespective of disease severity. Severe disease was observed frequently among children with LACV-ND. Seizures and AMS at presentation were independent predictors of severe disease. EEG may help determine long-term epilepsy risk. Long-term neurobehavioral issues are frequent and likely underrecognized among children with LACV-ND.